Awareness of Breast Cancer Screening among the Medical and General Population of the North Region of Cameroon - Richard Tagne Simo; Erika Myriam Baiguerel; Armel Hervé Nwabo Kamdje; Paul Faustin Seke Etet; Mohamadou Ahmadou; Charlette Nangue; Phelix Bruno Telefo (International Journal of Breast Cancer)
Breast cancer has become a real public health problem in Cameroon, particularly in rural areas due to late diagnosis, resulting partly from the absence of national screening programs. This work is aimed at assessing breast cancer awareness in the North Region of Cameroon. Participants were selected in six health centers surrounding the rural area of Garoua, North Region, Cameroon, and administered a questionnaire aimed at assessing their awareness about breast cancer risk factors and screening. Out of the 475 women (including 37 medical personnel) interviewed, 45.5% attended at least secondary school; 91.3% were aware of the disease with the main sources of information from those around them (64.8%), media (46.5%), and health professionals in health facilities (42.7%). 23.3% had misconceptions and myth-based ideas on the origin of the disease. Ignorance was the main reason preventing the performance of breast self-examination, and the high cost prevents individuals from going for mammography. The highest awareness rate was observed in employed women with higher level of education. Our study highlights the need to raise awareness among the populations in North Region, Cameroon, about the risk factors and clinical signs of breast cancer and the importance of screening practice for early diagnosis of breast cancer.